2004
DOI: 10.1039/b316437c
|View full text |Cite
|
Sign up to set email alerts
|

Embryonic development in the mouse is enhanced via microchannel culture

Abstract: Microfluidic devices (microchannels) have been fabricated and tested for embryo culture. Three different microfabrication materials (silicon, polydimethylsiloxane (PDMS), and borosilicate) were used to fabricate the microchannels. The objective of this study was to determine if static microchannels permitted culture of mouse embryos to the blastocyst stage. Groups of 10 two-cell ICR x B6SJL/F1 mouse embryos were cultured for 96 hours in 4 different physical culture systems: 1) silicon/borosilicate microchannel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
97
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 153 publications
(100 citation statements)
references
References 28 publications
3
97
0
Order By: Relevance
“…Microchannels have been used for several steps in the in vitro production of embryos typically either matching or improving the performance of previous methods. 1,2 Insect cell cultures as well have shown very different dimension dependent growth kinetics in microscale cultures as compared to macroscale flask cultures. 3 However, much of the previous culture work in microfluidics has focused on non-adherent (e.g., embryos, insect cells) or 2-D adherent cell culture in the absence of extracellular matrix.…”
Section: Introductionmentioning
confidence: 99%
“…Microchannels have been used for several steps in the in vitro production of embryos typically either matching or improving the performance of previous methods. 1,2 Insect cell cultures as well have shown very different dimension dependent growth kinetics in microscale cultures as compared to macroscale flask cultures. 3 However, much of the previous culture work in microfluidics has focused on non-adherent (e.g., embryos, insect cells) or 2-D adherent cell culture in the absence of extracellular matrix.…”
Section: Introductionmentioning
confidence: 99%
“…The use of HEK in toxicity assays (Chou et al 2002;Didier et al 1999;Monteiro-Riviere et al 2005;Rouse et al 2006;Shvedova et al 2003) makes this cell type an attractive candidate for use in microfluidic high throughput toxicity assays. Cell culture in microfluidic systems has been demonstrated by others Delamarche et al 2005;Figallo et al 2007;Flaim et al 2005;Folch and Toner 2000;Gu et al 2004;Hui and Bhatia 2007;Hung et al 2005a, Hung et al b;Kane et al 2006;Khademhosseini et al 2004;Kim et al 2006;Leclerc et al 2006a;b;Lee et al 2006;Prokop et al 2004;Raty et al 2004;Rhee et al 2005;Sin et al 2004;Song et al 2005;Toh et al 2007;Tourovskaia et al 2005;Walker et al 2002) but keratinocytes have not yet been studied at the microscale.…”
Section: Introductionmentioning
confidence: 99%
“…An alternate approach that permits a commercial means of utilizing microwells in conjunction with existing dishware in the lab involves using microwell-inserts consisting of several rows of tiny culture wells composed of PDMS [38]. Within PDMS and glass-bottomed microchannels under static media conditions, 2-cell mouse embryos can be cultured to the blastocyst stage [65,66]. However, researchers found that culture in microchannels resulted in significantly greater blastocyst formation and hatched blastocyst development at 72 h and 96 h, respectively.…”
Section: Embryo Culture Systems Using Pdms Chambers or Channelsmentioning
confidence: 99%
“…Within the last decade, studies using PDMS microfluidic channels or funnels have suggested novel solutions for oocyte manipulation, sperm sorting, and embryo culture . Microfluidic systems that mimic oviductal structures and functions for use in RT are divided into those used for sperm motility control or monitoring [50][51][52][53][54][55][56][57][58][59][60], regulation of chemical gradients for in vitro fertilization and embryo culture [61][62][63][64][65][66][67][68][69], and applying mechanical stimuli to the developing embryo [70][71][72][73][74]. Although the unique characteristics of elastomers have been exploited for microstructure fabrication and/or micro-pumping, mechanical deformation of the elastomer membrane has not been used to produce new devices for RT.…”
Section: Microfluidic Channels To Handle Sperm and Embryosmentioning
confidence: 99%